Exploring the Experiences of Family Caregivers of Children Hospitalized Due to Road Traffic Accident at Ho Teaching Hospital in Ghana - Asamoah, C. Y. (University of Ghana, 2024)
Family caregivers whose children are involved in road traffic accidents experience many challenges while taking care when they have been hospitalized. Some of which are emotional and psychological. This study seeks to explore and describe experiences of family caregivers caring for children hospitalized through road traffic accident at Ho Teaching Hospital, Ghana. Exploratory qualitative design was selected for the study using in- depth face to-face interviews. Purposive sampling was used to select respondents. Audio recordings were transcribed verbatim, cleaned and sorted into word document after which data was exported to Atlas.ti version 9 where themes and sub-themes were generated and analyzed. Overall, 4 main themes and 12 sub-themes emerged from the study. The major themes included, needs of family caregivers, tasks of family caregivers, beliefs and attitudes and health promotion behaviors. The study revealed that the respondents had different challenges for which support was warranted. Additionally, the caregivers indicated that they were solely responsible for performing their respective roles in protecting their children in a safe environment where they would grow. The respondents also disclosed that their belief in supernatural forces was a way of coping with their situations and helping them through their adversaries rather than it affecting them negatively. Further, they revealed that they receive different kinds support from different people which helps empower them and promote their well-being. Almost all the respondents indicated that they experienced some challenges while caring for their children involved in RTA with the majority being financial challenges however psychological challenges were the least. Nonetheless amidst all these challenges, they were all optimistic about full recovery. All stakeholders involved in child health care should build the capacity of caregivers to render safe and quality healthcare for these children.
MPhil. Nursing
Keywords: Family; caregivers; children; road traffic; Ho Teaching Hospital